Intra- and interspecific morphological diversity in Balanites (Balanitaceae) and Ziziphus (Rhamnaceae) across environmental gradients in Ethiopia - Seid, Mohammed Adefa; Nemomissa, Sileshi; Wondimu, Tigist (Phytotaxa, 2026)
Morphological traits provide critical insights for evolutionary and taxonomic studies. This study examined inter- and intraspecific morphological variation among Balanites and Ziziphus species collected across Ethiopia from January 2019 to June 2022. Up to three plant specimens per population were sampled 5–10 km apart and 50–100 m from roads. Morphological traits, bark colour, leaf shape and texture, fruit shape, and spine condition, were recorded. Environmental data were obtained from WorldClim v2, ISRIC, and FAO terrain datasets. Morphological data were analysed using hierarchical clustering (HC), principal component analysis (PCA), and redundancy analysis (RDA) in R 4.1.3. Hierarchical clustering (HC) identified five clusters in Balanites and eight in Ziziphus. Analysis of similarity (ANOSIM) confirmed significant dissimilarity among groups (Balanites: p = 0.001, R = 0.763; Ziziphus: p = 0.001, R = 0.938). The PCA revealed fruit shape, spine condition, and flower merosity as key traits in Balanites, while leaf base symmetry, bark colour, and leaf surface pubescence were important in Ziziphus. Redundancy analysis showed that environmental factors such as annual mean temperature (Bio01), isothermality (Bio03), and precipitation of the wettest quarter (Bio16) significantly affected Balanites morphology. For Ziziphus, temperature and precipitation-related variables, elevation, and topographic position index were significant contributors to variation. The findings highlight substantial morphological diversity within and between species of both genera, shaped by environmental gradients. Further studies of molecular phylogenetics and genetic diversity are recommended to support and expand these morphological insights.